Self-ish - O'Connor, Neely Bucknell, author; Thompson, Deborah, advisor; Levy, E. J., committee member; Kasser, Jeff, committee member (Colorado State University. Libraries, 2014)
Self-ish is a collection of essays surrounding the narrator's relationship to place, community, and family--the family one is born into and the family one chooses to create--and her evolving identity within these spaces. Essays include "The Cottage," which explores how the narrator's loss of innocence and feeling of community within her extended paternal family dissipates in conjunction with the sale of her family's cottage and the divorce of her parents. "Gone" is the story of the narrator's mentally ill and alcoholic father and her struggle to understand and accept him within the space of their sometimes-tumultuous relationship. In "B-Town, Bulgaria," the narrator chronicles her time studying abroad in Blagoevgrad, Bulgaria and the internal changes she experiences throughout her time there. "Misdirection" is a travel narrative that follows the narrator and her study abroad roommate, Kelli, to the Czech Republic as their friendship is tested and ultimately strengthened during their difficult travels. In "Jane," the narrator studies the differences between the relationships of friends and best friends by focusing on the relationship between herself and her best friend, Jane. The final essay, "#selfhelp," is a memoir essay that examines the narrator's relationship to the self-help community and how it both helps and hinders her.
Keywords: self-help; community; family; identity